2007
DOI: 10.1146/annurev.ecolsys.37.091305.110221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Behavior in the Evolution of Spiders, Silks, and Webs

Abstract: Spiders' silks and webs have made it possible for this diverse taxon to occupy a unique niche as the main predator for another, even more diverse taxon, the insects. Indeed, it might well be that the spiders, which are older, were a major force driving the insects into their diversity in a coevolutionary arms race. The spiders' weapons were their silks and here we explore the evidence for the evolution of silk production and web building as traits in spider phylogeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 111 publications
2
133
0
7
Order By: Relevance
“…The oldest fossils of the sole hosts of Pompilidae, spiders (Araneae), are found in the Carboniferous (360-290 Ma) (Selden et al 2013), with extant suborders and many sub-lineages found in Lower Jurassic fossils, ca. 175 Ma (Vollrath and Selden 2007;Penney and Selden 2011). Recent divergence-time estimation studies support the origin of crown-group spiders in the Late Devonian, and an origin for the majority of spider families before 100 Ma (Bond et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The oldest fossils of the sole hosts of Pompilidae, spiders (Araneae), are found in the Carboniferous (360-290 Ma) (Selden et al 2013), with extant suborders and many sub-lineages found in Lower Jurassic fossils, ca. 175 Ma (Vollrath and Selden 2007;Penney and Selden 2011). Recent divergence-time estimation studies support the origin of crown-group spiders in the Late Devonian, and an origin for the majority of spider families before 100 Ma (Bond et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This has significant evolutionary implications, 11,37 ensuring that debris or prey too large for the web to support will not cause irreparable damage, costing the spider energy to rebuild. Furthermore, the regulation of damage through control of material behavior has implications beyond webs to any structural design which would benefit from contained damage.…”
Section: Spider Web Mechanicsmentioning
confidence: 99%
“…Our interpretation of spigot location in Attercopus suggests that the original use of silk in protospiders was to produce such sheets, perhaps used as burrow linings, to cover egg masses (17), or as trails that would allow hunting animals to return to the safety of a retreat (18).…”
Section: Genetic Developmental Studiesmentioning
confidence: 99%